Grammar Writing: Definition & Introduction - Butt, Faiza; Sajid, Shazia (sourcecoder, 2023)
Language is an independent phenomenon, so that it is difficult to bind a language strictly by creating its grammatical structure. But, on the other hand, acquisition of another or a new language is not so possible without its grammatical rules, created or written by its grammarians. The primary role of grammar is to build and improve the speaking and writing skills of its learners. Indeed, it is no easy to define the main role played by grammar in the structure of a language, other than by using a metaphore such as ‘framework’. But no metaphore can deliver satisfactorily the different kinds of formal patterning and abstract relationship that are brought forward in a grammatical analysis. Search for the existence and the origin of "Proto Language.